PENGARUH KEPEMIMPINAN YANG KARISMATIK DAN JIWA BERWIRAUSAHA TERHADAP KEBERHASILAN USAHA (STUDI KASUS PADA USAHA MIKRO KECIL MENENGAH (UMKM) DI DESA LIMAU MANIS TANJUNG MORAWA DELI SERDANG) - Dewi, Lola Fransisca; Nasution, Lukman (JURNAL MUTIARA MANAJEMEN, 2022)
This study aims to determine the effect of charismatic leadership and entrepreneurial spirit on business success. The results showed that the entrepreneurial spirit (X2) had a positive effect on business success for MSME actors in Tanjung Morawa Village, Deli Serdang. This can be seen from the value of tcount > ttable (1.723 > 1.67528) with a significance of 5% or 0.05. Thus the decision taken is to accept the alternative hypothesis (H2) and reject the alternative hypothesis (H0). Together, the variables of charismatic leadership and entrepreneurial spirit have a significant influence on business success for MSME actors in Tanjung Morawa Village, Deli Serdang. This can be seen from the value of Fcount > Ftable (4.036 > 3.17 ) with a significant value of 5% or 0.05. Thus, the decision taken is to accept the alternative hypothesis (H3) and reject the alternative hypothesis (H0). The coefficient of determination value reached 0.39, meaning that it was able to explain the dependent variable of charismatic leadership and entrepreneurial spirit to the Independent variable, namely business success for MSME actors in Tanjung Morawa Village, Deli Serdang by 39% while 61% percent was explained by other variables not explained in the this study.